2020
DOI: 10.3389/fmars.2020.00618
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Stock Status of 16 Commercial Fish Species in the Coastal and Offshore Waters of Taiwan Using the CMSY and BSM Methods

Abstract: The waters around Taiwan are impacted by the Kuroshio and coastal currents, resulting in a high productivity and a high diversity of marine life. As a consequence, there are a multitude of fisheries around Taiwan, conducted by a fleet that has grown enormously in the last four decades. Here, we investigate the effect of the resulting fishing pressure on 16 commercial fish stocks including demersal and pelagic species in the coastal and offshore waters of Taiwan using the Monte Carlo Catch-Maximum Sustainable Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…By 2018, it had decreased to 16% (Figure 2). This dramatic decline can be attributed to high demand, unregulated fishing practices, and overexploitation [20,21]. In their evaluation of the stock status of 16 species under fishing pressure in the waters surrounding Taiwan, Ju et al [21] discovered only one species that is not overfished.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By 2018, it had decreased to 16% (Figure 2). This dramatic decline can be attributed to high demand, unregulated fishing practices, and overexploitation [20,21]. In their evaluation of the stock status of 16 species under fishing pressure in the waters surrounding Taiwan, Ju et al [21] discovered only one species that is not overfished.…”
Section: Introductionmentioning
confidence: 99%
“…This dramatic decline can be attributed to high demand, unregulated fishing practices, and overexploitation [20,21]. In their evaluation of the stock status of 16 species under fishing pressure in the waters surrounding Taiwan, Ju et al [21] discovered only one species that is not overfished. Furthermore, climate-driven environmental variabilities such as the El Niño-Southern Oscillation (ENSO) are pivotal factors affecting the intensity of the upwelling regions in the TB.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two methods have been applied to the assessment of fishery resources in China. One is the maximum sustainable yield (MSY) model, which uses a time series of catch and auxiliary data to estimate the MSY (Ju et al, 2020b;Liang et al, 2020;Zhai et al, 2020); The other is the length-based Bayesian biomass (LBB) model, which uses length frequency (LF) data to estimate asymptotic length, length at first capture, relative natural mortality and relative fishing mortality (Ju et al, 2020a;Kindong et al, 2020;Liang et al, 2020;Zhang et al, 2020Zhang et al, , 2021. Size measurement is the basic requirement for marine fishery resource surveys in China (Jin et al, 2012), and LF data are usually easier to obtain and cheaper than other data types (Liang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the fluctuation of these currents is strongly influenced by the seasonal monsoons and varied topography; consequently, the currents change the oceanographic conditions in the WT in different seasons (Lan et al, 2020b;Tseng et al, 2020). Biogeographically, the Taiwan Strait (TS) and waters off eastern Taiwan are migration routes for numerous pelagic fish species; therefore, their ecosystem dynamics and biogeochemical and physical processes vary substantially in space and time (Liao et al, 2018;Ju et al, 2020;Lin et al, 2020). The WT constitute excellent spawning, feeding, and overwintering habitats (Hsu et al, 2007;Madigan et al, 2016;Hsiao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This dramatic decline might be due to the high demand, unregulated fishing practices, or overexploitation of these species. Ju et al (2020) evaluated the stock status of S. commerson under fishing pressure in the WT and found that three stocks had collapsed. S. commerson species were classified as highly susceptible to the high levels of exploitation in the waters off eastern Taiwan (Lin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%